Cost-effective fibrinolytic enzyme production by microalga Dunaliella tertiolecta using medium supplemented with corn steep liquor - TÚLIO A.F. DA SILVA; PÁBLO E. DA C. E SILVA; THIAGO P. NASCIMENTO; ROMERO M.P.B. COSTA; ATTILIO CONVERTI; ANA LÚCIA F. PORTO; RAQUEL P. BEZERRA (Anais da Academia Brasileira de Ciências, 2023)
Abstract A fibrinolytic enzyme from the microalga Dunaliella tertiolecta was produced under mixotrophic conditions using different corn steep liquor (CSL) concentrations ( 0 ≤ CLS ≤ 0.75%), purified using a combination of salting out and ion-exchange chromatography, and then biochemical characterized. Cultivation of this microalga using 0.5% CSL led to the highest maximum cell concentration (1.960±0.010 mg L-1) and cell productivity (0.140g L-1 day-1), besides a high fibrinolytic activity of the extract obtained by the homogenization method (102 ±1 U mL-1). The enzyme extracted from the microalgal biomass was 5-fold purified with a 20% yield and was found to have a specific activity of 670 U mg-1. The enzyme, whose molecular weight determined by fibrin zymography was 10 kDa, was shown to be stable at pH 3.0–9.0 and up to 70°C with optimal pH and temperature values of 8.0 and 50°C, respectively. When compared to other fibrinolytic enzymes, this protease stood out for its high fibrinolytic activity, which was enhanced by Fe2+, inhibited by Zn2+, Cu2+, Mg2+, and Ca2+, and strongly inhibited by phenylmethylsulfonyl fluoride, suggesting that it belongs to the serine metalloprotease family. Moreover, thanks to its thermal stability, the enzyme may be easily preserved and activated under high-temperature conditions.